A new multimodal, image‐guided, robot‐assisted, interstitial brachytherapy for the treatment of head and neck tumors–A preliminary study. Issue 5 (6th July 2020) - Fanhao, Meng; Xiaodong, Xue; Bo, Qiao; Lejun, Xing; Yu, Song; Liang, Zhu; Tingting, Jia; Rui, Zhao; Depeng, Zhao; Ran, An; Yu, Tian; Suixin, Hu; et al.
Abstract: Background: Interstitial brachytherapy (BT) is becoming an accepted treatment option for head and neck cancer patients for whom surgery poses high risks. Multimodal, image‐guided, robotic surgery has the potential to allow precise seed implantation into tumors. Our aim was to introduce a new multimodal, image‐guided surgical robot during the performance of interstitial BT for the treatment of tumors in the head and neck regions. Methods: Clinical data for three patients were analyzed, retrospectively; patients had received 125 I seed implantations from July 2019 to October 2019. Multimodal, image‐guided, robotic surgery was performed in all patients. Postoperative computed tomography data were imported to software to evaluate the accuracy of the seed position and the operation times. Results: The mean placement error of the 125 I seed was 1.9 ± 0.74 mm. The mean operation time is 47 minutes. Conclusion: The experimental results showed that the Remebot has promise for use during BT for the head and neck.